(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A logbook is usually used to record borrowers or users who come in and out of the area in the College of Arts, Science and Engineering (CASE) Department facilities of Bestlink College of the Philippines. Radio Frequency Identification (RFID) is the non-contact wireless data transfer using radio frequency waves that allows for identification at a distance. This study focuses on implementing Universal RFID in a school management system limited to student access facilities, and it is intended to solve key issues in monitoring objects and equipment within the laboratories. This research used a qualitative approach to explore and provide deeper insights into the project and used a diagnostic research design to understand difficulties in the CASE Department and investigate the cause of a certain event to obtain information and create a possible solution for that event. This study also employs a developmental research design as a systematic study of designing, developing, and evaluating instructional programs, processes, and products that must meet internal consistency and effectiveness criteria. To demonstrate how closely software follows the design, we use ISO 25010 Systems and software quality requirements and evaluation, which specifies both software product quality and software quality in use, as well as practical recommendations on how to use the quality models. Based on observation and testing, the software appears to be of high quality in terms of effectiveness, efficiency, durability, maintainability, reliability, usability, functionality, portability, compatibility, and security. The software and the hardware are working properly, with no lags, delays, signal distortion, or errors. Furthermore, even when issues develop, all the data may be saved in the database and printed in hard copy at any time. The project is highly effective in monitoring variables such as teachers, students, and objects. Implementing this innovation would have a tremendous impact on our department’s school administration system and provide insight into how RFID can make monitoring, tracking, and recording much easier for other departments.